Nocturnal hypoxaemia in patients with Eisenmenger syndrome: a cohort study. Issue 3 (11th March 2013) - Ramakrishnan, Sivasubramanian; Juneja, Rajnish; Bardolei, Neil; Sharma, Ajay; Shukla, Garima; Bhatia, Manvir; Kalaivani, Mani; Kothari, Shyam S; Saxena, Anita; Bahl, Vinay K; Guleria, Randeep
Abstract : Objectives: The objective of the study was to find the prevalence of sleep-related disturbances in patients of Eisenmenger syndrome. Design: Prospective observational study. Setting: Tertiary care referral centre in North India. Participants: The study included 25 patients with Eisenmenger syndrome (mean age 25.2±9.6 years, 18 men) and 12 patients with cyanotic congenital heart disease with pulmonary stenosis physiology (mean age 20.5±8.5 years, 8 men) as controls. Interventions: All the patients underwent an overnight comprehensive polysomnogram study and pulmonary function testing. Main outcome measure: Oxygen desaturation index, which is the number of oxygen drops per hour. Results: The patients and controls had significant nocturnal hypoxaemia in the absence of apnoea and hypopnoea. The mean oxygen drop index in Eisenmenger syndrome group was 9.0±6.2 and in the control group was 8.0±5.9 (p=0.63). The apnoea–hypopnoea index was 3.37±5.0 in the Eisenmenger syndrome group and was 2.1±3.6 in the control group. Patients with >10 oxygen drops per hour had significantly higher haemoglobin (17.2±1.3% vs 14.4±1.5%, p<0.001) than those with oxygen drops less than 10. Conclusions: Eisenmenger syndrome patients have significant nocturnal hypoxaemia unrelated to hypopnoea and apnoea. Nocturnal desaturation occurred more frequently in patients with greater haemoglobin values.